Traumatic stress and post-traumatic growth in individuals who have had Covid-19: The mediating effect of resilience and moderating effect of psychological flexibility - Turk, Fulya (PUBLIC LIBRARY SCIENCE, 2024)
The Covid-19 pandemic has had a global impact and has negatively affected the mental health of individuals. It is known that depression, anxiety and traumatic stress levels are high in individuals who have experienced Covid-19. In light of this, an increase in Post-Traumatic Growth (PTB) levels is expected. This study examines the role of resilience and psychological flexibility in the relationship between traumatic stress levels experienced in Covid-19 and PTG levels. A total of 845 (64.18% males, ages ranged from 19 and 73, with an average of 36.80 +/- 8.43) adults from Turkiye participated in the online survey. Impact of Event Scale-Revised, The Posttraumatic Growth Inventory, The Psychological Resilience Scale, and Psychological Flexibility Scale were used as measurement tools. According to the research findings, a partial mediator role of resilience has emerged in the relationship between individuals' traumatic stress levels and PTG levels. Additionally, the regulatory function of psychological flexibility was determined in the relationship between traumatic stress levels and PTG levels. Accordingly, the link between Covid-19-related stress and PTG becomes stronger as the individual's psychological flexibility increases. Traumatic stress has a more positive effect on PTG in individuals who exhibit high psychological flexibility. Based on these results, it can be confirmed that resilience and psychological flexibility are crucial factors to maintain the spiritual well-being of individuals during the Covid-19 pandemic, a worldwide crisis. Therefore, they need to be considered in the field of preventive mental health.
Keywords: MENTAL-HEALTH; COMMITMENT THERAPY; PROTECTIVE ROLE; INFLEXIBILITY; DEPRESSION; PREVALENCE; ACCEPTANCE; SYMPTOMS; LOCKDOWN; ANXIETY; Science & Technology - Other Topics